Variations on the act of listening. Twenty-one orchestra audience development events in light of John Dewey's art as experience metaphor - Njörður Sigurjónsson 1974- (City University London, 2009)
Variations on the act of listening: Twenty-one orchestra audience development events in light of John Dewey’s ‘art as experience’ metaphor This thesis is a contribution to a critical debate about the role and impact of audience development theory on the organisation of orchestra concerts. It suggests that the conventional analysis of orchestra audience development, which is influenced by a marketing management tradition that favours the metaphor of ‘customer comfort’, is too reductive and that it gives the listening subject too limited a role in the process of music. In reaction to this, John Dewey‘s idea of ‘art as experience’ is introduced to open up the debate and explore the underlying assumptions of the prevailing arts marketing model of audience development. The thesis calls for a reform of the dominant audience development paradigm and the ‘toolbox’ conception of arts management. This thesis is based on the pragmatist aesthetic reading and interpretation of 21 orchestra events, concerts and educational performances, involving eight symphony orchestras. The orchestras are: the Berlin Philharmonic, the BBC Concert Orchestra, the Iceland Symphony Orchestra, the London Philharmonic Orchestra, the London Symphony Orchestra, the Orchestre de Paris, the Royal Philharmonic Orchestra and the San Francisco Symphony Orchestra. The 21 musical events were chosen on the basis of their diversity and representation of the variety of audience development activity that the symphony orchestras promote. Furthermore, the events have critical potential since they raise issues that are important to the understanding of what changes to the concert structure might mean in terms of a different understanding of audience development. The events are realisations of the fact that there are various ways of perceiving music through performance and listening. From the pragmatist perspective it is important that these variations on the classical concert form are not viewed or constructed as ideal, or more valuable in some abstract sense, ...